PERFIL DO CONSUMIDOR DE CARNE SUÍNA NA REGIÃO DO ALTO PANTANAL (ANASTÁCIO-MS) - Trindade, Vitória; Fonseca, Ariéli Daieny; Da Cruz, Gustavo; Baptista, Tânia Mara; De Arruda, Giovana; Pasquetti, Tiago Junior (ANAIS DO ENIC, 2018)
-